Study of impact levels of blue-green algae affected by different herbicides on fish in aquatic ecosystems - Loan, Nguyen Thi (Academia Journal of Biology, 2014)
This experiment was conducted to study the impacts of blue-green algae effected by different herbicides on the fish survival. The results showed that all of five herbicides (Butavi, Ronstar, Sofit, 2.4 D and Whip’s) expressed negative impacts with different levels on fish. Butavi affected the fish survival most seriously; sofit showed smallest impact and three other herbicides Ronstar, 2.4 D and Whip’s showed intermediate impact on fish survival.